Analisis Kebijakan Pembayaran Iuran Autodebet Rekening Peserta JKN-KIS Dalam Upaya Menurunkan Tunggakan Iuran Di Kabupaten Bengkulu Utara - Nanang Jayadi; Kamaludin Kamaludin; Fadli Fadli (Universitas Bengkulu, 2021)
The objectives of this study are (1) Knowing the implementation of the BPJS Kesehatan participant account auto debit payment policy in an effort to reduce dues arrears in North Bengkulu Regency and (2) Knowing the factors that influence the compliance of BPJS Kesehatan participants in paying dues in North Bengkulu Regency. This research is a type of survey research, namely research that takes a sample from a population using a questionnaire as a data collection tool. The type of data used is primary data obtained through a questionnaire. Research respondents were BPJS Kesehatan participants registered at the North Bengkulu Branch of BPJS Kesehatan. The method of taking respondents used is purposive sampling with the same proportion (proportional) consisting of 100 active participants and 100 inactive participants. So, the number of research respondents was 200 people. The sampling method used was a census. The data analysis method used is descriptive analysis and factor analysis. Based on the results of the data analysis, it is known that: (1) The implementation of the auto-debit account policy for BPJS participants has been quite effective in being selected as one of the modes of payment for BPJS contributions. The autodebet mode can be an alternative that makes it easy for participants to fulfill their obligations; and (2) reduction of the 27 initial factors obtained 8 factors that affect the compliance of BPJS Kesehatan participants in meeting the obligation to pay contributions. These factors are a combination and a combination of the initial factors which are grouped according to the factor rotation. These factors are: Demographic characteristics of BPJS participants, BPJS service administration factors, tariff factors and the ability to pay contributions; participant awareness factor; service trust factor; the factor of the sanction mechanism and law enforcement; factor of quality of medicine and factor of ease of service